IMPLEMENTASI KEPEMIMPINAN RESILIEN DI TK ISLAM TERPADU NURUL ILMI 1 TENGGARONG - Anisza Anisza; Nur Kholik Afandi; Nisrina Mutia Afifah (Jurnal Manajemen Pendidikan, 2026)
This research deeply analyzes the implementation of resilient leadership at TK Islam Terpadu Nurul Ilmi 1 Tenggarong. The institution is a small scale early childhood Islamic integrated school established in 2002 in Loa Ipuh Tenggarong East Kalimantan Province. It has successfully maintained A accreditation for five consecutive years while serving twenty nine active students under the leadership of Mrs Barinah S.H.I. The study adopts a qualitative descriptive case study method. Data were collected via participatory observation in-depth interviews as well as supervision records and analyzed using the Miles and Huberman model supported by triangulation techniques. Findings reveal that resilient leadership manifests in strategic planning through collaborative annual and semester program formulation aligned with child development standards and school vision. Operational management features flexible task distribution intensive team communication and adaptive RKAS budget planning prioritizing needs of educators students and facilities. Innovation in Islamic value formation integrates daily prayers hadiths project based learning with recycled materials calm corners and shadow teacher training for children with special needs. Strong parent partnerships are built through home visits and parenting programs.